PENGEMBANGAN SOAL HIGHER ORDER THINKING SKILLS SEBAGAI TES DIAGNOSTIK MISKONSEPSI MATEMATIS SISWA SMA - Benny Anggara (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
The need for developing students' higher order thinking skills is the main indicator in the application of HOTS-based questions in high school mathematics learning. The results of the implementation have not shown satisfactory results. The high level thinking ability of students in Indonesia in Mathematics is still very low. Therefore, a HOTS-based diagnostic test is needed which is able to detect the mathematical misconceptions of high school students as the aim of this study. Based on the research objectives, the method of this study is a qualitative method with research design using the Plomp model research design. The subjects of this study were several students and teachers at a school in Cirebon Regency. The results showed that four HOTS questions could be developed based on three aspects, namely, arithmetic, algebra, and geometry. The problem was developed to detect three forms of misconception, namely, theoretical, classification, and correlational misconceptions. The four questions that have been developed were assessed through the readability test of students and teachers, and CVR and CVI tests were carried out on eight mathematics teachers with valid results. Based on these results it can be concluded that the HOTS questions developed can be implemented for students to detect forms of mathematical misconceptions of high school students.